Study of the Effects of Heating on Organic Matter and Mineral Phases in Limestones - May-Crespo, J.; Martínez-Torres, P.; Quintana, P.; Alvarado-Gil, J. J.; Vilca-Quispe, L.; Camacho, N. (Journal of Spectroscopy, 2021)
Color-induced changes in stones due to heating can be useful in determining the degree of degradation generated in their components and structure. We evaluate the effect of heating in three types of limestones, useful in building and restoration, corresponding to biomicrite (BC), biosparite (BS), and intramicrite (IM), in the range of temperature from 100°C to 600°C. Our analyses indicate that the strongest changes in reflectance occur in the samples of intramicrite, followed by biomicrite, being biosparite showing the smallest ones. Additionally, IM samples suffer the largest modifications in effective porosity due to the thermal treatment; in contrast, BS and BC samples show smaller temperature-induced alterations associated with smaller changes in reflectance. Moreover, we reveal that most of the thermally induced variations are associated, in this range of temperature, to the dehydroxylation of goethite that transforms into hematite, as well as by the burning and partial release of the organic matter present in the rock. Colorimetry analyses show that the sequence of thermally induced changes can be followed by the evolution of the three coordinates, L∗ (lightness), a∗ (red-green), and b∗ (yellow-blue), of the CIE 1976 L∗a∗b∗ space.